Policy Challenges and Ethical Issues with the Breakthrough Technology: The Case of Synthetic Biology. (November 2017) - Pang, Samuel; Lee, Sam Youl; Seul, Ji Yung
Synthetic biology is an exciting field which has enormous potentials for solving various problems human beings are facing up such as genetic disease, food shortage and global warming. Many countries such as the United States, the United Kingdom and China have invested heavily in this field but the negative aspect of such scientific breakthrough draws little attention. Since the harms synthetic biology can cause is not certain, it is neither safe nor proper to leave it to the hands of only experts. Currently researches on synthetic biology are being conducted without proper public discourse and consideration. One of the reasons for the lack of public discussion on synthetic biology is the speed of the development in the field. The field is innovating so fast that people have little chance to digest the consequence of such advances. Also the confusion on the definition of synthetic biology contributes to the lack of proper public discussion on the issue. This article provides a new typology for definition of synthetic biology conceptualised by the authors and analyses the current state of synthetic biology in major countries. In addition, ethical issues associated with synthetic biology are discussed. Scientific transparency and participatory process are suggested as policy options to deal with them.